2017
DOI: 10.1016/j.actamat.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

The five-parameter grain boundary curvature distribution in an austenitic and ferritic steel

Abstract: The distribution of grain boundary curvatures as a function of five independent crystallographic parameters is measured in an austenitic and a ferritic steel. Both local curvatures and integral mean curvatures are measured from three dimensional electron backscattered diffraction data. The method is first validated on ideal shapes. When applied to real microstructures, it is found that the grain boundary mean curvature varies with the boundary crystallography and is more sensitive to the grain boundary plane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…[16,32]. Because of the terrace-step geometry of the interface created by the cube-shaped voxels, these interfaces are poor imitations of real grain boundaries, which are presumed to be smooth on a micron length scale.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,32]. Because of the terrace-step geometry of the interface created by the cube-shaped voxels, these interfaces are poor imitations of real grain boundaries, which are presumed to be smooth on a micron length scale.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…While this might be a reasonable approximation in some cases, it often fails to predict the motions of specific boundaries. 16 The method has been applied to two ferrous alloys and it was found that the curvature varies strongly as a function of the grain boundary plane orientation. In most work, H is assumed to be the inverse of the mean spherical equivalent grain radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained 3D model was then used to investigate microstructure behavior under various deformation conditions: uniaxial stretch, plane strain or uniaxial tension. The 3D EBSD was also recently used in other works focusing on metallic materials [42][43][44]. Similar research, but based just on the FIB/SEM was performed in [45], where authors used the FIB to reconstruct microstructure of porous metallic material or in [46] where primary carbides in the NiTa-Al-Cr-C alloy were investigated.…”
Section: 1mentioning
confidence: 97%
“…[1][2][3][4][5][6] Their mechanical properties, which are controlled by their microstructure, can be tuned relatively easily by thermomechanical processing. Ferrite is the first transformation product that forms during cooling as a result of austenite decomposition.…”
Section: Introductionmentioning
confidence: 99%